2011
DOI: 10.1021/es2006622
|View full text |Cite
|
Sign up to set email alerts
|

PMF Analysis of Wide-Range Particle Size Spectra Collected on a Major Highway

Abstract: Particle number concentration data have been collected on a very busy road in central London (Marylebone Road). Continuous size distributions from 15 nm to 10 μm diameter, collected over 21 days, were analyzed using positive matrix factorization which identified 10 factors, five of which were observed to make major contributions (greater than 8%) to either the total number or volume of particulate matter. The sources associated with each factor were identified from the size distribution, directional associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
169
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 201 publications
(190 citation statements)
references
References 21 publications
21
169
0
Order By: Relevance
“…For example, Charron and Harrison (2003) reported that particles in the range of 30-60 nm show a stronger association with light-duty traf- fic at a traffic hotspot in central London (Marylebone Rd); Janhäll et al (2004) reported an average particle size distribution peaking at 15-30 nm during morning peak high traffic intensity in the city of Göteborg (Sweden), which has a car fleet comparable to the UK; Ntziachristos et al (2007) found a sharp mode at 20-30 nm in sampling from engine exhausts. In addition, PMF factors with similar modal structures were found in other studies and were attributed to road traffic emissions: among others, Harrison et al (2011) linked a factor peaking at 20 nm to primary road traffic emissions near a major UK highway; Masiol et al (2016) measured PNSD in an international airport in northern Italy during summer and interpreted a factor with a clear mode at 35-40 nm as road traffic from the nearby city; Beddows et al (2015) and Vu et al (2016) found traffic factors with modal diameter at around 30 nm in an urban background site in London (North Kensington); Sowlat et al (2016) reported a factor peaking at 20-40 nm in number concentration and at around 30-40 nm in volume concentration in Los Angeles (US) and interpreted it as traffic tailpipe emissions. However, this factor lacks significant positive correlations with primary road traffic tracers (nitrogen oxides, eBC; Table 2), while other studies have reported weak positive correlations with such species Masiol et al, 2016;Vu et al, 2016;Sowlat et al, 2016).…”
Section: Warm Seasonsupporting
confidence: 76%
See 2 more Smart Citations
“…For example, Charron and Harrison (2003) reported that particles in the range of 30-60 nm show a stronger association with light-duty traf- fic at a traffic hotspot in central London (Marylebone Rd); Janhäll et al (2004) reported an average particle size distribution peaking at 15-30 nm during morning peak high traffic intensity in the city of Göteborg (Sweden), which has a car fleet comparable to the UK; Ntziachristos et al (2007) found a sharp mode at 20-30 nm in sampling from engine exhausts. In addition, PMF factors with similar modal structures were found in other studies and were attributed to road traffic emissions: among others, Harrison et al (2011) linked a factor peaking at 20 nm to primary road traffic emissions near a major UK highway; Masiol et al (2016) measured PNSD in an international airport in northern Italy during summer and interpreted a factor with a clear mode at 35-40 nm as road traffic from the nearby city; Beddows et al (2015) and Vu et al (2016) found traffic factors with modal diameter at around 30 nm in an urban background site in London (North Kensington); Sowlat et al (2016) reported a factor peaking at 20-40 nm in number concentration and at around 30-40 nm in volume concentration in Los Angeles (US) and interpreted it as traffic tailpipe emissions. However, this factor lacks significant positive correlations with primary road traffic tracers (nitrogen oxides, eBC; Table 2), while other studies have reported weak positive correlations with such species Masiol et al, 2016;Vu et al, 2016;Sowlat et al, 2016).…”
Section: Warm Seasonsupporting
confidence: 76%
“…It is recognised that road traffic contributes to a large range (30-200 nm) of PNSD in the urban atmosphere (e.g. Yue et al, 2008;Costabile et al, 2009;Harrison et al, 2011), which is compatible with these spectra. The directional analysis for the warm season shows increased levels when air masses move from the sectors more affected by traffic, i.e.…”
Section: K Means Cluster Analysismentioning
confidence: 60%
See 1 more Smart Citation
“…This includes a large proportion of extra-urban highway traffic, where wear emissions are expected to be lower than in the urban environment with its frequent stop-and-go driving and cornering. Estimates of the contribution of nonexhaust particles to total vehicle-generated particulate matter are in the range of 35-55% (Harrison et al, 2001;Charron and Harrison, 2005;Harrison et al, 2011). Recently, Rexeis and Hausberger (2009) predicted, using a detailed emission model for the Austrian fleet, that the percentage of PM nonexhaust of the total PM emissions will increase from about 50% between 2005 and 2010 up to some 80-90% by 2020.…”
Section: Emissionsmentioning
confidence: 99%
“…To simulate the real situation of the atmosphere and to understand the exact environment problem, many researchers have developed air quality models and statistical methods recently. Using Receptor Model [5]- [7] and Source Model [8], [9] to evaluate the pollutant concentrations and emission. Source Model divides into three categories.…”
Section: Introductionmentioning
confidence: 99%